Possibilities of using Moringa (Moringa oleifera) Seed Meal as a Partial Substitute for Groundnut Cake in Broiler Diets and its Effect on Growth Performance of Broiler Chicks - Manju,; Khinchi, Rakesh Kumar; Karnani, Monika; Meena, Sarjna (International Journal of Bio-resource and Stress Management, 2025)
The experiment was conducted from February to March, 2018 at Poultry unit of CVAS, Udaipur (Rajasthan), to investigate the possibilities of using Moringa oleifera Seed Meal (MOSM) as a partial substitute for groundnut cake in broiler diets and its effect with or without using an acidifier as a feed additive on the growth performance of broiler chicks. A feeding trial of 42 days was conducted on 300 broiler chicks in a 5×2 factorial design. The dietary treatments were basal diet as control without MOSM (T1), basal diet with MOSM @ 1% (T2), 2% (T3), 3% (T4), 4% (T5), basal diet with Acidifier @ 1 g kg-1 feed (T6), basal diet with MOSM @ 1, 2, 3 and 4% with Acidifier @ 1 g kg-1 feed for T7, T8, T9 and T10, respectively. Highly significant (p<0.01) effect of dietary treatments i.e. inclusion of MOSM at different levels on body weight, body weight gain, average daily gain, performance index, protein efficiency ratio, nitrogen balance, digestibility of dry matter, crude protein, ether extract and crude fiber were observed. However, the effect of MOSM in the broiler ration on feed conversion efficiency and protein efficiency ratio was observed to be significant (p<0.05). The effect of acidifier on dry matter digestibility was observed to be significant (p<0.05). It was concluded that MOSM with or without an acidifier can be incorporated in the broiler’s diet without any adverse effect on the growth performance of the broiler chicks.